Shakespear’s Employment of Malapropism in “Much ado about Nothing”and The Merchant of Venice” - Raheel, Marzooqa T.; Abd, Zahraa Ammar (Journal of Ecohumanism, 2024)
Malapropism, according to the Encyclopedia Britannica, is a linguistic mistake occurs when one term is replaced with another that sounds similar but has a different meaning. The current article aims to find out how malapropism is used in Shakespear’s “Much ado about Nothing “and “The Merchant of Venice “and to investigate the most common type of malapropism used in these two plays .The article mainly draws on Fay and Cutler’s(1977) division of malapropism to analyze the selected data. The study concludes that malapropism is used by the plays’ characters basically to create a sense of humor by using a word or a phrase that is different from what they intended to say .It was also found that classical malapropism is the most common used type in both selected plays.